Effect of Sperm DNA Fragmentation on Embryo Quality in Normal Responder Women in In Vitro Fertilization and Intracytoplasmic Sperm Injection - Kim, Su Mi; Kim, Seul Ki; Jee, Byung Chul; Kim, Seok Hyun (Yonsei medical journal, 2019)
To investigate the associations between sperm DNA fragmentation (SDF) and embryo formation rate in normal responder women to in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). Fifty-three consecutive, fresh IVF/ICSI cycles performed from 2014 to 2017 were selected. All women were normal responders (4 to 14 mature oocytes were retrieved) and at least one normally fertilized oocyte with two pronuclei was obtained in all cycles. Semen was collected on the day of oocyte retrieval, and SDF levels were measured by sperm chromatin dispersion test (Halosperm assay). At day 3 after insemination, embryo quality was evaluated by morphologic criteria and categorized as A/B/C/D. Top quality embryo were defined as grade A embryos with seven cells or more. SDF levels showed a positive linear correlation with the male's age (r=0.307, =0.025) and a negative linear correlation with sperm motility (r=-0.491, <0.0001). To achieve top-quality or a grade A embryo formation rate >70%, the cut-off value SDF was <30.7% for each. Among individuals with SDF <30.7%, the median top-quality or grade A embryo formation rate was significantly higher than that among individuals with SDF ≥30.7% (38.1% vs. 20.0%, =0.038; 50% vs. 25.0%, =0.017). In normal responder women, high SDF level resulted in low day 3 embryo formation rates. Our results suggest a paternal effect on embryo quality in IVF/ICSI cycles.